Physical Stability Test Spray 10% Combination of Virgin Coconut Oil (VCO) and Ginger (Zingiber Officinale Rocs.) As a candidate of a substance for the cure of gingivitis - Ashfi Salsabila; Khusnul Munika Listari (Eduvest - Journal of Universal Studies, 2026)
Virgin Coconut Oil (VCO) and ginger (Zingiber officinale Rosc.) have antibacterial and anti-inflammatory activities, making them potential natural alternative therapies for the treatment of gingivitis. Although their biological effectiveness has been proven, the physical stability of this combination spray preparation has not yet been evaluated. The spray formulation was chosen because it is practical, provides even distribution, and minimises contamination. To determine the effect of physical stability testing of a 10% VCO-ginger spray combination as a candidate material for the treatment of gingivitis. Laboratory experimental research was conducted by creating five formulations (F1-F5). Stable formulations were subjected to a cycling test and physical stability evaluation, including organoleptic testing, homogeneity, pH, viscosity, spreadability, and adhesion. Data analysis was performed descriptively. Formulation F5 showed the best physical characteristics with a milky white colour, a distinctive coconut-ginger smell, a homogeneous liquid texture, a pH of 6.019-6.823, a spreadability of 5.0-6.1 cm, an adhesion of 19.27-29.72 seconds, and a viscosity of 346.7-692.8 cP. Formulation F5 has physical performance potential as a candidate for gingivitis therapy, but its emulsion stability is limited under extreme temperature conditions. Optimisation of surfactant concentration is required to prevent viscosity reduction and phase separation during long-term storage.